Occupational accidents related to gender in the village of La Xuyen wood handicraft - Truong Thi, Ly (Indonesian Social Work Consortium (ISWC), 2022)
One of the main craft groups in Vietnam is carpentry. According to research conducted in the La Xuyen wood handicraft village, accidents at work—from minor mishaps to serious and serious accidents—are quite common in the wood industry. Fatal workplace incident According to research, there are numerous hazards that could result in work accidents for both male and female employees in La Xuyen craft village. Men and women differ in that men experience more workplace accidents, and men also experience a higher rate of occupational accidents than women. This is because men frequently take on heavier tasks and use potentially flimsy machinery. Whereas women frequently take on simple, creative jobs that call for ingenuity and use few machines.